SCABIES WITH SECONDARY BACTERIAL INFECTION IN A BOARDING SCHOOL STUDENT: A CASE REPORT - Imaroh, Rifa; Lumaksono, Maria Angela; Imani, Izzah; Widasmara, Dhelya (GoAcademica Research dan Publishing, 2025)
Scabies is a contagious parasitic skin disease caused by Sarcoptes scabiei var. hominis. A 14-year-old male student residing in an Islamic boarding school presented to a public health centre with a long-standing history of scab-like skin lesions. The patient had sought treatment for more than one month without clinical improvement. He complained of intense nocturnal pruritus affecting the interdigital spaces and palms, accompanied by erythematous lesions, excoriations, vesicles, purulent discharge, swelling, pain, and fever. He also reported pain in the axillary and inguinal regions. Physical examination revealed multiple discrete erythematous papules and vesicles on the interdigital spaces and palms, accompanied by crusts, excoriations, and purulent discharge. Enlarged and tender axillary lymph nodes were also noted. Based on clinical findings, the patient was diagnosed with scabies complicated by secondary bacterial infection. Non-pharmacological management included patient and family education regarding the disease, personal hygiene, environmental sanitation, and a visit to the boarding school to prevent further transmission. Pharmacological therapy consisted of oral antibiotics, analgesics, antihistamines, and anti-inflammatory agents. Topical treatment included anti-scabietic therapy and a combination of topical antibiotic and anti-inflammatory agents. Scabies may be complicated by secondary bacterial infection due to delayed diagnosis and treatment, persistent scratching, and poor personal and environmental hygiene. Overcrowded living conditions, such as those in boarding schools, facilitate transmission and increase the risk of complications. A family-centred and community-based approach, particularly involving boarding school environments, plays a crucial role in controlling transmission and improving outcomes in patients with scabies complicated by secondary infection.